2021
DOI: 10.21203/rs.3.rs-315078/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mucopolysaccharidosis VII in Brazil: Natural History and Clinical Findings

Abstract: Background: Mucopolysaccharidosis type VII (MPS VII), also known as Sly syndrome, caused by deficiency of the lysosomal enzyme β-glucuronidase, is an ultra-rare disorder with scarce epidemiological data and few publications about natural history and clinical spectrum. Methods: We conducted a case series report which included retrospective data from all MPS VII patients diagnosed through the “MPS Brazil Network” who were known to be alive in 2020 in Brazil (N=13). Clinical data were obtained from a review of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Table 3 shows that MPS VII had the lowest incidence values in all cases. These observations agree with what is found in the literature, since it is considered an ultra‐rare disease, with a prevalence of <1:1 000 000 41 . The incidence value found in our study is higher than that reported in the United States and Taiwan but is similar to that previously reported by Zielonka et al 42 of 0.01.…”
Section: Resultssupporting
confidence: 93%
“…Table 3 shows that MPS VII had the lowest incidence values in all cases. These observations agree with what is found in the literature, since it is considered an ultra‐rare disease, with a prevalence of <1:1 000 000 41 . The incidence value found in our study is higher than that reported in the United States and Taiwan but is similar to that previously reported by Zielonka et al 42 of 0.01.…”
Section: Resultssupporting
confidence: 93%